Lung cancer among coal miners, ore miners and quarrymen: smoking-adjusted risk estimates from the synergy pooled analysis of case-control studies - Dirk Taeger; Beate Pesch; Benjamin Kendzia; Thomas Behrens; Karl-Heinz Jöckel; Dirk Dahmann; Jack Siemiatycki; Hans Kromhout; Roel Vermeulen; Susan Peters; Ann Olsson; Irene Brüske; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: Working in mines and quarries has been associated with an elevated lung cancer risk but with inconsistent results for coal miners. This study aimed to estimate the smoking-adjusted lung cancer risk among coal miners and compare the risk pattern with lung cancer risks among ore miners and quarrymen. METHODS: We estimated lung cancer risks of coal and ore miners and quarrymen among 14 251 lung cancer cases and 17 267 controls from the SYNERGY pooled case-control study, controlling for smoking and employment in other at-risk occupations. RESULTS: Ever working as miner or quarryman (690 cases, 436 controls) was associated with an elevated odds ratio (OR) of 1.55 [95% confidence interval (95% CI) 1.34-1.79] for lung cancer. Ore miners (53 cases, 24 controls) had a higher OR (2.34, 95% CI 1.36-4.03) than quarrymen (67 cases, 39 controls; OR 1.92, 95% CI 1.21-3.05) and coal miners (442 cases, 297 controls; OR 1.40, 95% CI 1.18-1.67), but CI overlapped. We did not observe trends by duration of exposure or time since last exposure. CONCLUSIONS: This pooled analysis of population-based studies demonstrated an excess lung cancer risk among miners and quarrymen that remained increased after adjustment for detailed smoking history and working in other at-risk occupations. The increase in risk among coal miners were less pronounced than for ore miners or quarrymen.